General, Applied and Systems Toxicology 2009
DOI: 10.1002/9780470744307.gat152
|View full text |Cite
|
Sign up to set email alerts
|

Ricin: Chemistry, Sources, Exposures, Toxicology and Medical Aspects

Abstract: The chapter covers the origins of ricin toxin, which is present in the seeds of the many cultivars of the castor oil plant. The structure and biogenesis of the dimeric (A and B chain toxin) ricin (RCA 60 ) is described, compared with the related, but less toxic, Ricinus agglutinin (RCA 120 ) and the toxic activity of ricin, the N ‐glycosidase activity of the A chain, is explained. The intoxication process is further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…A significant number of fatal and sub-lethal cases of human intoxication have been reported following accidental or deliberate ingestion or from parenteral exposure to ricin [ 4 ]. The development of prophylactic and post-exposure therapies for ricin intoxication has been on-going for many years [ 5 , 6 ] and a continued requirement for the development of medical countermeasures for ricin has been identified [ 7 ]. At present, however, there is no specific prophylactic or post-exposure therapy available for the clinical management of individuals exposed to ricin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of fatal and sub-lethal cases of human intoxication have been reported following accidental or deliberate ingestion or from parenteral exposure to ricin [ 4 ]. The development of prophylactic and post-exposure therapies for ricin intoxication has been on-going for many years [ 5 , 6 ] and a continued requirement for the development of medical countermeasures for ricin has been identified [ 7 ]. At present, however, there is no specific prophylactic or post-exposure therapy available for the clinical management of individuals exposed to ricin.…”
Section: Introductionmentioning
confidence: 99%
“…The toxin then enzymatically inactivates the ribosome though depurination of a single adenine residue in the 28 S ribosomal subunit. This event inactivates the 60 S ribosomal subunit, disrupts protein synthesis and results in cell death [ 1 , 6 ]. A single ricin molecule has been hypothesised to have the potential to inactivate multiple ribosomes and consequently killing a cell [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Castor seeds contain notable amounts of ricin ranging (depending on the origin of the seeds) from 0.1% to 4.0% of the weight of the bean . For the manufacturing of castor oil, ricin has to be deactivated.…”
Section: Introductionmentioning
confidence: 99%
“…12 Castor seeds contain notable amounts of ricin ranging (depending on the origin of the seeds) from 0.1% to 4.0% of the weight of the bean. 13 For the manufacturing of castor oil, ricin has to be deactivated. Deactivation of ricin occurs during the extraction process if the temperature used is higher than 80 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in rodents and non-human primates demonstrated that following pulmonary exposure to lethal dose of ricin, the injury is mostly confined to the lungs, including marked interstitial pneumonia associated with pro-inflammatory cytokine release, massive neutrophil infiltration, vascular hyperpermeability, perivascular and alveolar edema, hemorrhages, diffuse airway epithelial cell and alveolar macrophage death. Eventually, the extensive pneumonia, which involves massive cell infiltration and excessive accumulation of pleural fluids leads to respiratory insufficiency and death [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . This damage to the lungs is classified as acute lung injury, which can develop to acute respiratory distress syndrome (ARDS) 12 .…”
mentioning
confidence: 99%